SVP besois d'aide

A = 9x - 7 + 2x + 5

B = −3a + 12 − ( 6a + 7 )

C = 6c² − 17c + 8 − ( 5c ² − 3c ) + ( 17c − 14 )

D = 3 (2e + 7 )

E = 8k ( k − 3 ) + 12

F = −9 ( 5 + v ) − 7 ( 2v² + 5 )

les x ne sont pas des fois c'est la lettre x.

2

Réponses

2014-03-29T09:28:41+01:00
Salut :)

A = 9x - 7 + 2x + 5
A = 7x - 2

B = −3a + 12 − ( 6a + 7 )
B = -3a + 12 - 6a - 7
B = -9a + 5

C = 6c² − 17c + 8 − ( 5c ²  − 3c ) + ( 17c − 14 )
C = 6c² - 17c + 8 - 5c² + 3c + 17c - 14
C = c² + 3c - 6

D = 3 (2e + 7 )
D = 3 x 2e + 3 x 7
D = 6e + 21

E = 8k ( k − 3 ) + 12
E = 8k x k + 8k x (-3) + 12
E = 8k² - 24k + 12

F = −9 ( 5 + v ) − 7 ( 2v² + 5 )

F = -9 x 5 - 9 x v - 7 x 2v² - 7 x 5
F = -45 - 9v - 14v² - 35
F = -14v² - 9v - 80

J'espère t'avoir aidé(e)! :)
2014-03-29T10:32:49+01:00
A = 9x - 7 + 2x + 5
A = 7x - 2

B = - 3a + 12 - (6a + 7)
B = -3a + 12 - 6a - 7
B = - 9a + 5

C = 6c² − 17c + 8 − ( 5c ²  − 3c ) + ( 17c − 14 )
C = 6c² - 17c + 8 - 5c² + 3c + 17c - 14
C = c² + 3c - 6

D = 3 (2e + 7)
D = 6e + 21

E = 8k (k − 3) + 12
E = 8k² - 24k + 12

F = −9 (5 + v) - 7 (2v² + 5)

F = - 45 - 9v - 14v² - 35
F = -14v² - 9v - 80